Investigation of Dynamics in BMIM TFSA Ionic Liquid through Variable Temperature and Pressure NMR Relaxometry and Diffusometry. Issue 8 (11th May 2017) - Pilar, Kartik; Rua, Armando; Suarez, Sophia N.; Mallia, Christopher; Lai, Shen; Jayakody, J. R. P.; Hatcher, Jasmine L.; Wishart, James F.; Greenbaum, Steve
Abstract : A comprehensive variable temperature, pressure and frequency multinuclear ( 1 H, 2 H, and 19 F) magnetic resonance study was undertaken on selectively deuterated 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide (BMIM TFSA) ionic liquid isotopologues. This study builds on our earlier investigation of the effects of increasing alkyl chain length on diffusion and dynamics in imidazolium-based TFSA ionic liquids. Fast field cycling 1 H T1 data revealed multiple modes of motion. Through calculation of diffusion coefficient (D) values and activation energies, the low- and high-field regimes were assigned to the translational and reorientation dynamics respectively. Variable-pressure 2 H T1 measurements reveal site-dependent interactions in the cation with strengths in the order MD3 > CD3 > CD2, indicating dissimilarities in the electric field gradients along the alkyl chain, with the CD2 sites having the largest gradient. Additionally, the α saturation effect in T1 vs. P was observed for all three sites, suggesting significant reduction of the short-range rapid reorientational dynamics. This reduction was also deduced from the variable pressure 1 H T1 data, which showed an approach to saturation for both the methyl and butyl group terminal methyl sites. Pressure-dependent D measurements show independent motions for both cations and anions, with the cations having greater D values over the entire pressure range.